2014
DOI: 10.1590/s0100-204x2014000900005
|View full text |Cite
|
Sign up to set email alerts
|

Determinação do volume de madeira em povoamento de eucalipto por escâner a laser aerotransportado

Abstract: Resumo -O objetivo deste trabalho foi avaliar a possibilidade de se estimar o diâmetro à altura do peito (DAP) com os dados de altura e de número de árvores derivados do escâner a laser aerotransportado (LiDAR, "light detection and ranging"), e determinar o volume de madeira de talhão de Eucalyptus sp. a partir dessas variáveis. O número total de árvores detectadas foi obtido com uso da filtragem de máxima local. A altura de plantas estimada pelo LiDAR apresentou tendência não significativa à subestimativa. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
10
0
7
Order By: Relevance
“…Os dados de altura, DAP e volume obtidos pelo MGO das árvores foram submetidos à análise de variância a 5% de probabilidade e os dados de alturas e DAP foram comparados mediante superposição das barras do erro-padrão da média de cada tratamento (OLIVEIRA et al, 2014).…”
Section: Ima = V/t [1]unclassified
“…Os dados de altura, DAP e volume obtidos pelo MGO das árvores foram submetidos à análise de variância a 5% de probabilidade e os dados de alturas e DAP foram comparados mediante superposição das barras do erro-padrão da média de cada tratamento (OLIVEIRA et al, 2014).…”
Section: Ima = V/t [1]unclassified
“…In Brazil, the fact that eucalyptus plantations are mainly destined for pulping or energy purposes, as well as the fast growth conditions of the country, means that the applicability of the proposed models is limited to young plantations (around 7 years or less) grown in high densities (around 1,111 trees per hectare). For instance, the following works all present height-diameter models for eucalyptus grown in Brazil using data from stands ages 8 years and younger: Ribeiro et al, 2010;Thiersch et al 2013;Miranda et al, 2014;Oliveira et al 2014;Mendonça et al, 2015;Souza et al, 2016. While there are some exceptions of studies dealing with older plantations (Azevedo et al, 2011;Oliveira et al, 2015) these are generally from small plantations that have not received active management operations (such as thinning or fertilization).…”
Section: Introductionmentioning
confidence: 99%
“…Martins Neto et al (2013) observed tendencies of underestimation for the diameters in upper parts of the trunk using data obtained with terrestrial LiDAR. Oliveira et al (2014), using aerial LiDAR, reported tendency to underestimate the trees height in 5%, and total timber volume in the stand in 11.4%. Buck et al (2012) and Buck et al (2014) reported that the presence of branches resulted in decrease in the density of points, mainly in the upper parts of trees, hindering the 3D modeling.…”
Section: Discussionmentioning
confidence: 95%